Thinking Skills for Professionals - Greetham, B. author. aut Link
XVI, 290 p.
Keywords: This book gives professionals and business people the essential tools to become better thinkers and decision-makers. It sets out simple methods and techniques to avoid poor decision making by developing our conceptual, creative and critical thinking skills, along with ways of incorporating them within our daily lives.